PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA (PERFORMANCE) ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH PEMILU 2009 KABUPATEN PURWOREJO. - , Moh Amri Rosjid, ST; , Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Theoretically, there are many factors that are able to influence the performance. Nevertheless, by seeing the phenomena happening in the field, it can be stated that the performance of the Indonesian Legislative Assembly Member at Purworejo Regency at general election 2009 is more influenced by the education and training toward the Indonesian Legislative Assembly Member at Purworejo Regency of general election 2009. This research is aimed to find out the greatness of influence for education and training toward the performance of the Indonesian Legislative Assembly Member at Purworejo Regency of general election 2009. Based on the grade of explanation, this research belongs to the regression research with the approach of survey (survey research). The subject which will be researched is the members of the Indonesian Legislative Assembly at Purworejo Regency period of 2009-2014. Meanwhile the object of this research is the education and training of Indonesian Legislative Assembly Members at Purworejo and the influence toward the performance of the members. The population on this research is all the members of the Indonesian Legislative Assembly at Purworejo Regency period 2009-2014. The technique of taking the sample which is used on this research is census method. By this method, all of population members that are 44 members, are also the sample of research. The collection of data is done by questioner, interview and documentation. The data analysis technique is descriptive analysis and double linier regression analysis with test F, test t, and test of determination. The result of research shows that the education and training have the positive and significant influences toward the performance of members of Indonesian Legislative Assembly at Purworejo Regency General Election 2009. The dominant variable that gives influence is training. It is about 79,5% performance of the Indonesian Legislative Assembly Members of Purworejo Regency General Election 2009 directly is influence by the education and training, meanwhile the rest about 20,5% (100%-79,5%) is influenced by other factors that are not estimated on this research.